Crepidotus iqbalii (Crepidotaceae, Agaricales) a new stipitate species, from Pakistan - Izhar, Aiman; Usman, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2021)
Crepidotus iqbalii is described as a new species based on specimens collected from Sheikhupura, Punjab, Pakistan. Morphological techniques and phylogenetic analyses based on nrITS sequences were used to confirm the novelty of the species. The key characters of C. iqbalii include growth on soil, a bright brown to yellow, hygrophanous pileus, a distinct central to slightly eccentric stipe, ellipsoid-amygdaliform, almost smooth to slightly verruculose basidiospores, presence of cheilo-, pileo- and caulocystidia but absence of pleurocystidia, and clamp connections present in all tissues.